Pemanfaatan Media Sosial Instagram Sebagai Sarana Promosi Untuk Meningkatkan Brand Awareness Pt Eshta Yudha Ekatama Indonesia (EYE Indonesia) - Nabilla, Nabilla Rahmawati; Kristiana Widiawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study is to examine how EYE Indonesia utilizes the social media platform Instagram to enhance brand awareness. EYE Indonesia is a company engaged in out-of-home (OOH) advertising and uses digital platforms to expand its advertising reach. This research adopts a descriptive qualitative approach, collecting data through observation and interviews. The use of engaging visual content and the utilization of Instagram features such as Stories, Reels, and Feed, as well as active audience interaction contribute significantly to enhancing brand awareness. This integrated promotional strategy helps strengthen the company’s image as a professional and innovative out-of-home media service provider. In conclusion, Instagram-based promotional strategies have proven effective in increasing EYE Indonesia's brand awareness amid growing industry competition.